TORAKOCHIRURGIASurgical treatment of air leak after pulmonary resection - Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Air leak is one of the most common complications occurring after pulmonary resection. Risk factors as well as methods of prevention and surgical treatment are discussed. Based on the author’s experience and overview of the literature the following conclusions were drawn: preoperative identification of high-risk patients, careful dissection of pulmonary fissures and immediate surgical suturing of parenchymal and bronchial air leak together with the use of sealants are the most important factors leading to significant reduction of postoperative pulmonary air leak.